SOCIOSCIENTIFIC ISSUES AS A PEDAGOGICAL APPROACH TO FOSTER SCIENTIFIC ARGUMENTATION IN BIOPLASTIC PRODUCTION USING SUGARCANE BAGASSE - Salsafitri, Medina Fasya; Sunarya, Risa Rahmawati; Helsy, Imelda; Dahriah, Iis (UIN AR-RANIRY, 2025)
This study aims to develop students’ scientific argumentation through the implementation of socioscientific issues-based learning in the production of bioplastics from sugarcane bagasse (Saccharum officinarum). The method employed is pre-experimental with a one-shot case study design. The research subjects consisted of 36 eleventh-grade students from the Industrial Chemistry program at a vocational high school (SMK) in Cimahi City. The research instruments included student activity observation sheets, student worksheets, argumentation debates, and scientific argumentation tests. Students’ activities during the learning process showed excellent results, with an average score of 94. Meanwhile, their ability to complete the student worksheets achieved an average score of 98, both falling into the “very good” category. The majority of students’ oral argumentation was at level 2, which includes a claim supported by evidence without rebuttal. In contrast, the development of students’ written scientific argumentation after the implementation of socioscientific issues was at quality level 3, characterized by arguments that include weak rebuttals. These findings indicate that socioscientific issues-based learning can be effective in developing students’ scientific argumentation, although further instruction is needed to enhance students’ ability to present stronger, evidence-based rebuttals.